Effects of bio-fertilizers and putrescine on some physiological and biochemical traits of wheat (Triticum aestivum L.) under water limitation condition - Alireza Mohseni Mohammadjanlou; Raouf Seyed Sharifi; Saeid Khomari (تنش های محیطی در علوم زراعی, 2023)
IntroductionWater limitation is one of the most important environmental factors in reducing the growth and yield of wheat due to producing reactive oxygen species and reducing membrane stability (El-Tayeb, 2006). Several strategies have been suggested in order to improve grain yield of wheat under water limitation condition, among them use of bio fertilizers and putrescine play a key role in yield improvement. PGPR and Mycorrhiza fungi have the potential to modulate and regulate the physiological and biochemical responses of plants against drought stress, and for this reason, they increase plant survival under environmental conditions (Marasco et al., 2012). Polyamines are another compound that play a significant protective role in plants when environmental stress occurs (Hadi et al., 2016). Foliar of putrescine is able to improve the resistance of plants in oxidative stress and by increasing the activity of antioxidant enzymes, it increases the resistance of plants against oxidative stress (Groppa et al., 2001). A better understanding of physiological responses under water limitation condition may help in programs which the objective is to improve yield of wheat. During the course of these stresses, active solute accumulation of compatible solutes such as proline and the activities CAT, POD and PPO enzymes are claimed to be an effective stress tolerance mechanism. Therefore, the aim of this study was to evaluate the effects of bio fertilizers and putrescine on some the physiological and biochemical responses (i.e., antioxidant enzyme activity, soluble sugars, proline, malondialdehyde (MDA) and hydrogen peroxide (H2O2) content) of wheat under water limitation.Materials and methodsA factorial experiment was conducted based on randomized complete block design with three replications at the research farm, faculty of Agriculture and Natural Resources, University of Mohaghegh Ardabili during 2018-2019. Factors experiment were included irrigation at three levels (full irrigation as control, irrigation withholding in 50% of heading stage and irrigation withholding in 50% booting stage as moderate and severe water limitation respectively) and bio fertilizers at four levels [no bio fertilizer, both application of Psedomunas Putida Strain 186 and Flavobacterim Spp, both application of Mycorrhiza with Psedomunas and Flavobacterim, application of Mycorrhiza], and putrescine foliar application in three levels (foliar application with water as control and foliar application 0.5 and 1 mM of putrescine). Psedomunas putida strain 186 and Flavobacterim spp were isolated from the rhizospheres of wheat by Research Institute of Soil and Water, Tehran, Iran. For inoculation seeds were coated with gum Arabic as an adhesive and rolled into the suspension of bacteria until uniformly coated. The strains and cell densities of microorganisms used as PGPR in this experiment were 1×107 colony forming units (CFU). Mycorrhiza fungi (Glomus intraradices) was purchased from the Zist Fanavar Turan institute. The activity of antioxidant enzymes (catalase, peroxidase and polyphenol oxidase) was measured by Sudhakar et al. (2001) method, soluble sugar content by Dubios et al. (1956) method, measurement of malondialdehyde (MDA) by Stewart and Bewley, (1980) and method of Alexieva et al, (2001) was used to measure the hydrogen peroxide. Proline content was measured by Bates et al. (1973) method. Analysis of variance and mean comparisons were performed using SAS9.1 computer software packages. The main effects and interactions were tested using the least significant difference (LSD) test at the 0.05 probability level.Results and discussionApplication of both Mycorrhiza with Pseudomonas and Flavobacterium and putrescine foliar application under severe water limitation conditions (irrigation withholding in booting) increased the activity of polyphenol oxidase, peroxidase and catalase enzymes. The highest activity of these enzymes were obtained in irrigation withholding in booting stage with application of both Mycorrhiza with Pseudomonas and Flavobacterium and foliar application of 1 mM putrescine and the lowest of values were obtained in full irrigation and no application of bio fertilizers and no putrescine foliar application. The highest rates of proline and soluble sugar were observed under irrigation withholding in heading with the both application of biofertilizers and putrescine and the lowest of them were observed in full irrigation, no application of biofertilizers and no foliar putrescine. Water limitation increased electrical conductivity (EC), malondialdehyde (MDA) and hydrogen peroxide (H2O2) content, while application of bio fertilizers and putrescine under water limitation conditions decreased electrical conductivity, malondialdehyde and hydrogen peroxide content. Application of Mycorrhiza with Pseudomonas and Flavobacterium and foliar of 1 mM putrescine under severe water limitation decreased malondialdehyde and hydrogen peroxide content about 51 and 31.72% respectively compared to no application biofertilizers and putrescine under same water limitation level. In general, water limitation (irrigation withholding in booting and heading) decreased grain yield compared to full irrigation. application Pseudomonas and Flavobacterium (23.1%) and both application of Mycorrhiza with Pseudomonas and Flavobacterium (16.6%) increased grain yield in comparison with no application of biofertilizers under conditions of irrigation withholding in booting. Foliar application 1 mM of putrescine increased grain yield about 8.5% in comparison with no application putrescine.ConclusionIt seems that application of bio fertilizers and putrescine can increase grain yield of wheat under water limitation conditions due to improving physiological and biochemical trait.